The Red Frock - Ilaria Vanni (PORTAL: Journal of Multidisciplinary International Studies)
In this reflection, I recount my experience supervising a UTS student in Milan during her In-Country Study, where I became a luxury fashion faux buyer as part of her research on luxury shopping. An unexpected encounter in a high-fashion boutique taught me the importance of attentive observation and developing tools to help students make sense of complex global and local interactions. This moment reinforced my appreciation for elevating experiences in teaching and the value of speculative thinking in understanding the interconnectedness of global capitalism, culture, and place.